Working in beta: testing urban experiments and innovation policy within Dublin city council. - McDermott, Fiona (Springer Open, 2019)
This chapter describes Dublin City Council (DCC) Beta, an initiative developed as part of the City Council's Architects' Division to experiment, innovate and quickly test ideas directly 'on the street'. Through the detailing of a number of Beta Projects, it illustrates how a project is initiated, what the key processes are, what the role of the citizen is and how the outcomes of completed projects are measured and formalised. It also discusses the Beta Model, highlighting the opportunities and challenges that such a model present for other city governments. Ultimately, it addresses the question of how such an initiative can increase the potential for more inclusive, immediate and innovative approaches to urban problems in a context of risk-averse city governments with increasing constraints of both resources and finance alongside a growing demand for greater democratic authorship and ownership of the built environment.
Keywords: Stadtsoziologie; Urban governance; Kommunalpolitik; Stadtverwaltung; Partizipation; Stadtgesellschaft; Stadtgestaltung; Projektbeispiel